Pengaruh Pengembangan Karir dan Beban Kerja Terhadap Prestasi Kerja Karyawan Pada PT. PLN (Persero) UP3 Kota Bima - Muamal Tupriatna; Wulandari; Mukhlis (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of career development and workload on employee performance at PT. PLN (Persero) UP3 Bima City. The high workload at PT. PLN (Persero) UP3 Bima City can be seen that every month they have a target that must be achieved. This research is included in the category of associative research using a quantitative approach with a sample of 47 people. Based on the results of the partial test (t test) and simultaneous test (F test) it can be said that there is a positive and significant influence on career development on employee performance at PT. PLN (Persero) UP3 Bima City. If career development and workload decrease, employee performance will also decrease.